Privacy and Security Risks in Cross-Border Digital Payment Systems - Naeem AllahRakha; Tillayeva Gulsanam Xamdamovna; Bozarov Sardor Sokhibjonovich; Otabek Narziev; Pulatov Temurbek (Faculty of Law, University of Muhammadiyah Malang, 2025)
This research examines the privacy and security concerns associated with the growing adoption of digital payments. Digital payments represent a new development in payment systems being assessed by institutions, companies, and individuals. The worldwide adoption of digital payments necessitates a thorough examination of the privacy and security risks associated with these systems, particularly those operating under different regulatory frameworks. This research identifies gaps in current laws and major weaknesses in privacy and security protections, with a focus on risks to user rights. Using a mixed-methods approach, the study includes a qualitative analysis of relevant data protection laws along with a quantitative survey of user concerns and awareness. It examines practical issues and combines insights using grounded theory. The findings indicate a heavy dependence on central regulation and varying privacy standards, resulting in more frequent violations that restrict user protections and avenues for recourse. This research suggests establishing global privacy and security standards for digital payments, supported by strong enforcement and collaboration between countries. These standards should provide clear data practices, give users control over their personal information, implement robust security measures, and encourage the use of new technologies that enhance privacy. The study concludes that careful governance and cooperation are crucial for the safe development of cross-border digital payment systems, while mitigating risks to privacy, security, and user rights.